Chronicle updates in cyclodextrin-based carriers for drug delivery - Singh, Jatinder (2023)
The significant emergence of novel drugs for effective diagnosis and treatment finds a common difficulty, i.e. successful drug targeting and delivery in the desired target area. Most of the commercialized drug molecules lack solubility, specificity, permeability, immediate metabolism and lesser tolerability, making the drug lacking therapeutic eminence (Hodgson 2001; Loftsson and Brewster 2010). The development of modified drug formulation has been proven to overcome the drawbacks of drugs with above-mentioned problems. Many research works have been initiated to bring out novel drug carrier molecules to meet the requirements. Cyclodextrins (CDs) as three-dimensional molecule are one of the highly explored drug delivery/carrier systems as biomedical application